PENGASUHAN ANAK USIA DINI PADA KELUARGA PETANI - Ahmad Syauki; Ichsan Ichsan; Winarti Winarti (Thufuli, 2022)
Every child has the right to get the best care and education in every phase of his age. But in reality, not all parents understand how to properly care for their children. The purpose of this study was to find out how to care for early childhood in farming families in Karumbu Village, Langgudu District, Bima Regency. This research is a descriptive qualitative research, by making four farming families as research subjects. The method of collecting data is through observation and in-depth interviews. The results showed that, family 1 used an authoritarian and permissive form of parenting for their 5-year-old child, while for their 2-year-old child she used democratic parenting. then Families 2, 3, and 4 use the same form of parenting, namely democratic. The findings in this study are the application of parenting provided by parents depending on the age of the child.